Metabonomic profiling of clubroot-susceptible and clubroot-resistant radish and the assessment of disease-resistant metabolites - Li, Jingwei; Huang, Tingmin; Lu, Jinbiao; Xu, Xiuhong; Zhang, Wanping (Frontiers in Plant Science, 2022)
Plasmodiophora brassicae causes a serious threat to cruciferous plants including radish (Raphanus sativus L.). Knowledge on the pathogenic regularity and molecular mechanisms of P. brassicae and radish is limited, especially on the metabolism level. In the present study, hairy root initial infection of resting spores (107 CFU/mL) at 24 h post-inoculation and root club symptom arising at cortex splitting stage were identified. We demonstrated changes in metabolite regulation and pathways during the cortex splitting stage of diseased roots between clubroot-susceptible and clubroot-resistant cultivars using un-targeted metabonomic analysis. We identified a larger number of differentially regulated metabolites (DRMs) and heavier metabolite profile changes in the susceptible cultivar than in the resistant counterpart. The metabolites that were differentially regulated in both cultivars were mostly lipids and lipid-like molecules. Significantly regulated metabolites and pathways according to the P value and variable important in projection (VIP) score were identified. Moreover, four compounds, including ethyl α-D-thioglucopyranoside, imipenem, ginsenoside Rg1, and 6-gingerol, were selected, and their anti-P. brassicae ability and effects on seedling growth were verified on the susceptible cultivar. Except for ethyl α-D-thioglucopyranoside, the remaining could inhibit root club development. The use of 5 mg/L ginsenoside Rg1 + 5 mg/L 6-gingerol resulted in the lowest disease incidence among all treatments and enhanced plant growth. The regulation of pathways or metabolites of carbapenem and ginsenoside was further explored. The results provide a preliminary understanding of the interaction between radish and P. brassicae at the metabolism level, as well as the development of measures for preventing clubroot.